Tinjauan tentang dampak inflasi terhadap keputusan berdasarkan pencatatan biaya historis di Neraca - Kafi Rijal; Insyirah Munawwar (PT. Arsil Reka Engineering, 2023)
In an agency that has not used an Information System, usually the preparation of the report is often not on time and the presentation of the report often experiences errors in recording the nominal amount of the transaction. Fulfillment of the information needs of the management at a certain time cannot be fulfilled because the data is still in the form of a lot of paper archives, so that in searching for the data it is difficult, therefore agencies can experience delays in providing transaction report data to superiors. An agency must use a lot of computers as a means of supporting the office. In order to assist in maximizing management performance in matters of financial reporting. In this case agencies can take advantage of several applications that can be used, one of which is an Information System that can assist in recording financial transactions. Information systems that must be able to include a series of collections - a collection of reports on cash source activities and a summary of receipts, cash disbursements for a certain period to present information on the use of cash with the aim of reporting to internal parties as a basis for making decisions about plans for the future.